The Burden of Human Papillomavirus Infections and Related Diseases in Sub-Saharan Africa - Vuyst, Hugo De; Alemany, Laia; Lacey, Charles; Chibwesha, Carla J.; Sahasrabuddhe, Vikrant; Banura, Cecily; Denny, Lynette; Parhami, Groesbeck P.* (ELSEVIER, 2014)
abstract Despite the scarcity of high quality cancer registries and lack of reliable mortality data, it is clear that human papillomavirus (HPV)-associated diseases, particularly cervical cancer, are major causes of mor bidity and mortality in sub-Saharan Africa (SSA). Cervical cancer incidence rates in SSA are the highest in the world and the disease is the most common cause of cancer death among women in the region. The high incidence of cervical cancer is a consequence of the inability of most countries to either ini tiate or sustain cervical cancer prevention services. In addition, it appears that the prevalence of HPV in women with normal cytology is higher than in more developed areas of the world, at an average of 24%. There is, however, significant regional variation in SSA, with the highest incidence of HPV infection and cervical cancer found in Eastern and Western Africa. It is expected that, due to aging and growth of the population, but also to lack of access to appropriate prevention services and the concomitant human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) epidemic, cervical cancer incidence and mortality rates in SSA will rise over the next 20 years. HPV16 and 18 are the most com mon genotypes in cervical cancer in SSA, although other carcinogenic HPV types, such as HPV45 and 35, are also relatively more frequent compared with other world regions. Data on other HPV-related anogenital cancers including those of the vulva, vagina, anus, and penis, are limited. Genital warts are common and associated with HPV types 6 and 11. HIV infection increases incidence and prevalence of all HPV-associated diseases. Sociocultural determinants of HPV-related disease, as well as the impact of forces that result in social destabilization, demand further study. Strategies to reduce the excessive burden of HPV-related diseases in SSA include age-appropriate prophylactic HPV vaccination, cervical cancer prevention services for women of the reproductive ages, and control of HIV/AIDS. This article forms part of a regional report entitled “Comprehensive Control of HPV Infections and Related Diseases in the Sub-Saharan Africa Region”Vaccine Volume 31, Supplement 5, 2013. Updates of the progress in the field are presented in a separate monograph entitled “Comprehensive Control of HPV Infections and Related Diseases” Vaccine Volume 30, Supplement 5, 2012.
Keywords: HPV epidemiology; Cervical cancer; Anogenital cancers; Genital warts; Sub-Saharan Africa